(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The article examines the principles of visualizing idioms in ideographic dictionaries, including the selection of expressions, methods of their graphical representation, and the correlation of figurative meaning with visual images. The role of visualization in increasing clarity, facilitating the acquisition of idioms, and developing students’ language intuition is emphasized.